Protein Folding and Function: The N-Terminal Fragment in Adenylate Kinase - Kumar, Sandeep; Sham, Yuk Yin; Tsai, Chung-Jung; Nussinov, Ruth (Biophysical journal, 2001)
Three-dimensional protein folds range from simple to highly complex architectures. In complex folds, some building block fragments are more important for correct protein folding than others. Such fragments are typically buried in the protein core and mediate interactions between other fragments. Here we present an automated, surface area-based algorithm that is able to indicate which, among all local elements of the structure, is critical for the formation of the native fold, and apply it to structurally well-characterized proteins. In particular, we focus on adenylate kinase. The fragment containing the phosphate binding, P-loop (the “giant anion hole”) flanked by a β-strand and an α-helix near the N-terminus, is identified as a critical building block. This building block shows a high degree of sequence and structural conservation in all adenylate kinases. The results of our molecular dynamics simulations are consistent with this identification. In its absence, the protein flips to a stable, non-native state. In this misfolded conformation, the other local elements of the structure are in their native-like conformations; however, their association is non-native. Furthermore, this element is critically important for the function of the enzyme, coupling folding, and function.